2012
DOI: 10.5586/aa.2012.067
|View full text |Cite
|
Sign up to set email alerts
|

The share of xerothermic species in vascular flora of the city of Lublin (Poland)

Abstract: A b s t r a c tThe purpose of this study is to present the distribution and characteristics of xerothermic flora located within Lublin (51 o 08'-51 o 18'N and 22 o 27'-22 o 41E). The data on this flora have been derived from the literature and herbarium collections as well as they were collected during field research conducted in 2002-2009. Family affiliation, life forms, geographical-historical groups, the degree of synanthropization of species and habitat, categories of threat are discussed in this paper. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The UHI is associated with therophytes, alien plants including thermo-and heliophilous species, and areas with dense development. The study has shown a diversity of thermal preferences of the vascular plants of Lublin, which is characteristic for major urban areas [20][21][22]30,40,[53][54][55][56][57]. The average temperature indicator values for the floras of the study areas in the Lublin center (CzH, LSq) and suburban area (DF) are close to the values reported by Wittig and Durwen [56] and Witosławski and Bomanowska [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The UHI is associated with therophytes, alien plants including thermo-and heliophilous species, and areas with dense development. The study has shown a diversity of thermal preferences of the vascular plants of Lublin, which is characteristic for major urban areas [20][21][22]30,40,[53][54][55][56][57]. The average temperature indicator values for the floras of the study areas in the Lublin center (CzH, LSq) and suburban area (DF) are close to the values reported by Wittig and Durwen [56] and Witosławski and Bomanowska [57].…”
Section: Discussionmentioning
confidence: 99%
“…In total, the contemporary flora of the Lublin City area included 1,052 vascular plant species. Among them, there is the group of thermophilous and heliophilous species including 194 xerothermic and psammophilous grassland species, and 236 therophytes [30,40]. The proportion of squares with presence of the species analyzed varied between the different habitats in the whole Lublin area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anemone sylvestris, the rare species of xerothermic grassland, exhibited decrease in the number of individuals, in the abundance of flowering, considerable changes in pollen properties and in the seed production in the case of two out of the three populations studied. The reduction in individuals of A. sylvestris was exacerbated by the expansion of the shrub community, dominated by Prunus spinosa, Cornus sanguinea, or Rhamnus cathartica L. Similarly, in other studies, dominance of the shrub communities on xerothermic patches was responsible for the decrease in the population size of many species, especially heliophytes [5][6][7]60]. The shrub removing intervention undertaken by local authority to prevent grassland overgrowing contributed to the tendency towards restoration of numerous individual plants of A. sylvestris.…”
Section: Discussionmentioning
confidence: 99%
“…These habitats significantly contribute to the biodiversity of both flora and fauna [4][5][6]. The xerothermic vegetation has become strongly endangered, dramatic losses are due to habitat destruction, fragmentation, secondary succession, or even competition from invasive species [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%